IMPLEMENTASI PERATURAN PEMERINTAH NOMOR 27 TAHUN 2012 TENTANG IZIN LINGKUNGAN SEBAGAI INSTRUMEN DALAM MEWUJUDKAN PEMBANGUNAN BERKELANJUTAN DI KABUPATEN KAMPAR - Hendri, Mutia Fadhillah; Firdaus, Emilda; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Research on Government Regulation No. 27 of 2012 on the environmental permit is the study focused on the realization of the implementation or execution of policy, namely the realization of the policy in issuing environmental permits. The main problem and focus as the basis of the research and preparation of this paper is to investigate, find and analyze the implementation of the Government Regulation No. 27 of 2012 as one of the instruments to achieve sustainable development in Kampar regency.This research is a sociological law because it describes the legal issues in the implementation of granting environmental permits in Kampar. This research was conducted in Kampar regency, population and sample in this research is the secretary of the commission IV Kampar regency, secretary, the Environment Agency (BLH) Kampar regency, initiator and community. Source of data in this study used primary data and secondary data, data collection techniques in this study with interviews and review of the literature.From the results of this study concluded, to achieve sustainable development in Kampar district is not yet fully operational meet the requirements as stipulated in Government Regulation No. 27 of 2012 on the environmental permit. Inhibiting factors in the implementation of granting environmental permits in Kampar absence of clear tariffs for the manufacturing and process approval environmentally feasible for EIA and / or recommendation of UKL-UPL, the absence of local regulations most related to the implementation of the issuance of the environmental permit, exclusion of the public in making framework references in the issuance of the environmental permit as already set out in Government Regulation No. 27 of 2012 on the environmental permit, as well as sanctions against businesses that do not have environmental permits in Kampar regency shaped only rebuke and writing.Keywords : implementation, environmental permits, sustainable development